WATER QUALITY STUDIES FOR IRRIGATION ON SUB WATERSHEDS NGARAK WATERSHEDS MANDOR - vivin, florianus selvinus; Saifudin, Saifudin; Widiarso, Bambang (Fakultas Pertanian Universitas Tanjungpura, 2013)
Watersheds is an area where all the water goes into the river that separated by topography, watershed condition at an area will show the conditions that exist in the surrounding environment. This study aims to determine the classification spesific water for irrigation in the watershed Ngarak District Overseer. This research was done in two (2) outlets located on the watershed Ngarak Mandor District outlet A and outlet B. The study took place from December 2012 until May 2013, with a total area of approximately 6,750 ha. This study begins by collecting biophysical data that includes classroom watershed slope, soil type, land use, rainfall and agriculture. The Method of water quality analysis has done of direct measurements in the field and laboratory measurements with observational parameters include: Salinity, Boron, SAR, RSC, temperature, water pH, flow discharge, Brightness, alkalinity, and Content of Sediments. The measurement results of water samples showed an average salinity values ??ranged from 0.0073 ds / m - 0.077 ds / m, the average level of Boron ranged from 0.017 mg / l - 0.018 mg / l. Average SAR values ??ranged from 1.003 to 1.486, the average RSC ranged between 0.0062 meq / l - 0.0314 meq / l, and a supporter of the variables, the average water temperature ranged between 26.68 C0 - 27, 12 C0, the average pH of the water ranged from 6.73 to 6.85, the average flow discharge ranged from 0.979 m3/second - 2,017 m3/second, Brightness average water ranged from 48.6 cm - 110.8 cm, and alkalinity ranged from an average of 5.26 mg / l - 7.18 mg / l and the average content of sediments ranged from 5.4 mg / l - 18.8 mg / l. Based on the analysis and calculation of the main variables and the supporting variables, the water Watershed District Overseer Ngarak can be used for irrigation because it is based on the classification of the suitability of water for irrigation, watershed Ngarak Mandor District on appropriate criteria for irrigation class.